A new paradigm for virtual knowledge sharing in product development based on emergent social software platforms. (November 2018) - Evans, Richard David; Gao, James Xiaoyu; Martin, Nick; Simmonds, Clive
The UK Government considers its Aerospace Industry a remarkable success story, enjoying a global market share of 17% in 2015. The capture, management and sharing of employee knowledge is seen as vital if the industry is to remain highly innovative and retain its pre-eminent position internationally. Aerospace manufacturers, such as BAE Systems, often have to re-engineer business processes routinely to ensure their survival. Knowledge sharing in the industry is seen as challenging due to the dispersed nature of its operations and multi-tier supply chains. This article, through a 5-year participant-observation study at the World's second largest aerospace and defence organisation, BAE Systems, proposes a new paradigm for virtual knowledge sharing in dispersed aerospace product development based on emergent social software platforms such as Enterprise 2.0 technologies. The developed framework and methodologies are applied to the bespoke BAE Systems' engineering lifecycle process to validate its effectiveness with results indicating that Enterprise 2.0 technologies offer a more openly innovative environment in which employees may share and interact with knowledge more effectively and easily across geographical and functional boundaries, compared with conventional engineering information systems.